Role of increased neutrophil extracellular trap formation on acute kidney injury in COVID-19 patients - Kim, In Soo; Kim, Do Hyun; Lee, Hoi Woul; Kim, Sung Gyun; Kim, Yong Kyun; Kim, Jwa-Kyung (Frontiers in Immunology, 2023)
Background: A strong association between elevated neutrophil extracellular trap (NET) levels and poor clinical outcomes in patients with coronavirus infection 2019 (COVID-19) has been reported. However, while acute kidney injury (AKI) is a common complication of COVID-19, the role of NETs in COVID-19-associated AKI is unclear. We investigated the association between elevated NETs and AKI and the prognostic role of NETs in COVID-19 patients. Methods: Two representative markers of NETs, circulating nucleosomes and myeloperoxidase-DNA, were measured in 115 hospitalized patients. Serum levels of interleukin [IL]-6, monocyte chemotactic protein-1 [MCP-1], plasma von Willebrand factor (vWF) and urinary biomarkers of renal tubular damage (β2-microglobulin [β2M] and kidney injury molecule 1 [KIM-1]) were measured. Results: AKI was found in 43 patients (37.4%), and pre-existing chronic kidney disease (CKD) was a strong risk factor for AKI. Higher circulating NET levels were a significant predictor of increased risk of initial ICU admission, in-hospital mortality (adjusted HR 3.21, 95% CI 1.08–9.19) and AKI (OR 3.67, 95% CI 1.30-10.41), independent of age, diabetes, pre-existing CKD and IL-6 levels. There were strong correlations between circulating nucleosome levels and urinary KIM-1/creatinine (r=0.368, p=0.001) and β2M (r=0.218, p=0.049) levels. NETs were also strongly closely associated with serum vWF (r = 0.356, p<0.001), but not with IL-6 or MCP-1 levels. Conclusions: Elevated NETs were closely associated with AKI, which was a strong predictor of mortality. The close association between NETs and vWF may suggest a role for NETs in COVID-19-associated vasculopathy causing AKI.